Shaping the role and democratic responsibility of the wojt (rural commune mayor), city mayor, or city president as a local leader (legal and political aspects) - Kasiński, Michał (Acta Universitatis Lodziensis. Folia Iuridica, 2015)
The present study shows the process of shaping the concept of local leadership in Poland, which concerns mayors of rural communes, mayors and presidents of cities, directly elected by citizens − and their role as local government executive leaders. Particular attention is paid to legal and political mechanisms of their election and political (democratic) responsibility towards the citizens. In these mechanisms, there have been detected factors which substantially weaken social trustworthiness of the role of the leader and its democratic advantages. These factors especially include a low rate of vote turnout (both in local election and in referenda for dismissal from any of the offices listed above) and various informational manipulations aimed at distorting the true picture of public opinion in these matters. The author has pointed to dysfunction of regulations and political phenomena, which cause that the concept of a local leader in Poland has met very serious difficulties in practice and is not trusted by the community.